2011
DOI: 10.1002/cmdc.201000510
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile and Practical Synthesis toward the Development of Novel HIV‐1 Integrase Inhibitors

Abstract: As a continuation of our previous work, which resulted in the identification of a new hit compound as an HIV-1 integrase inhibitor, three novel series of salicylic acid derivatives were synthesized using three versatile and practical synthetic strategies and were assayed for their capacity to inhibit the catalytic activity of HIV-1 integrase. Biological evaluations revealed that some of the synthesized compounds possess good inhibitory potency in enzymatic assays and are able to inhibit viral replication in MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…[6] Apart from these clinically approved drugs, numerous other 2-aryl-, 2-alkyl-5-aryl-and 2,5-diarylfurans have been investigated as drug candidates in medicinal chemistry studies over the past decade. These compounds ( Figure 2) were tested for diverse applications, such as activity against several cancer cell lines (compounds 5 and 6), [7] cardioprotective activity through inhibition of Na + /H + exchangers (7), [8,9] activity as an HIV-integrase inhibitor (8), [10,11] activity against Mycobacterium tuberculosis (9) [12] or as potential therapeutics for smoking cessation (10). [13] [a] Universität Potsdam, Institut für Chemie (Organische Synthesechemie Because of the low to moderate yields normally observed for Meerwein arylation reactions of furans, this method is restricted to cheap or conveniently available starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Apart from these clinically approved drugs, numerous other 2-aryl-, 2-alkyl-5-aryl-and 2,5-diarylfurans have been investigated as drug candidates in medicinal chemistry studies over the past decade. These compounds ( Figure 2) were tested for diverse applications, such as activity against several cancer cell lines (compounds 5 and 6), [7] cardioprotective activity through inhibition of Na + /H + exchangers (7), [8,9] activity as an HIV-integrase inhibitor (8), [10,11] activity against Mycobacterium tuberculosis (9) [12] or as potential therapeutics for smoking cessation (10). [13] [a] Universität Potsdam, Institut für Chemie (Organische Synthesechemie Because of the low to moderate yields normally observed for Meerwein arylation reactions of furans, this method is restricted to cheap or conveniently available starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…Methyl 4-(5-formylfuran-2-yl)-2-hydroxybenzoate ( 5 ) was obtained through Suzuki reaction between commercially available 3 (methyl 4-iodosalicylate) and compound 4 (5-formyl-2-furanylboronic acid), subsequent basic hydrolysis furnished the acid analogue ( 6 ). Derivatives 9a-f , were synthesized using a recently published [ 18 ] multicomponent protocol that includes nucleophilic displacement between the opportune amine and trithiocarbonate ( 7 ) to form the substituted rhodanine intermediates ( 8a-f ), followed by Knoevenagel condensation with aldehyde ( 6 ) catalysed by an excess of primary amine ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…As reported in Table 1 , compound 2 was found to be active at low nanomolar concentrations (11–13 nM) on both NL4.3 and AD8 HIV strains also in CD4 + human lymphocytes, while showing a CC 50 of 810 nM and thus a selectivity index of 62. Interestingly, in contrast to raltegravir, compound 2 maintained similar EC 50 values also on integrase mutating recombinant viruses, thus suggesting that the strong antiviral activity of the series of rhodanine derivatives could not be ascribed to integrase inhibition [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by studies showing that small molecules or peptides are able to interfere with crucial protein-protein interactions involved in the biology of viruses [14][15][16][17][18][19][20], bacteria [21] and parasites [22,23]. In addition, small-molecules inhibiting protein interaction networks were identified as potential drugs in cancer treatment and some of them reached preclinical and clinical trials [24] Indeed small-molecule antagonists of p53-MDM2 interaction have been shown to be able to inhibit tumor growth induced by an overproduction of MDM2.…”
Section: Protein-protein Interactions and New Drug Targetsmentioning
confidence: 87%